Universidade vivenciada na cidade: estudantes da Unioeste em Marechal Cândido Rondon/PR (1994-2009) - Reisdörfer, Thiago (2011)
This search discusses youth experiences of students from Universidade Estadual do Oeste do Paraná (West Paraná State University), Unioeste, campus of Marechal Cândido Rondon/PR, on the Brazil and Paraguay border, analyzing the temporal clipping from 1994 to 2009. The University, commonly conceived as an desire field, it is assumed, however, in this work, as a place of multiple conflicts, tensions, exchanges and dialogues, evaluating the meanings that the joining in this social life circumstances assumes in the students narratives from many places of this region and country. The University and the Marechal Cândido Rondon town were reported as a place of intercultural experiences, trying not losing the idea that this space is usually and concomitantly a social space as well as desired. This way, the University is experienced in and through the city, and this problematic can highlight specific issues concerning the historicity of those experiences. About these issues, it is paid more attention tothe multiple and complex relationships between the university students coming from other cities to live there with different social groups in the city. The methodology terms are emphasizedin the use of oral sources, discussing memories of young university students from the theoretical-methodological contributions of the Oral History. These discussions are shown in this research in a dialogic way and mainly concerned on three points: first, to discuss the multiple paths and expectations that led youths to Unioeste and Marechal Cândido Rondon; then, it is given special attention to intercultural experiences in the relationship between the city and University; and, at last, it isanalyzed verge experiences about the moment of the graduation conclusion.